Social Enterprises and Health Care Services within the European Legal Framework - Alceste Santuari (Review of European and Comparative Law)
Social enterprises (SEs) are organizations that pursue a purpose of general interest through the carrying out of economic activities on a steady and permanent basis. Despite the legal, economic and social differences among the Member States (MSs) of the European Union, SEs display at least two similar characteristics. Firstly, SEs are capable of combining entrepreneurial activities together with the pursuit of a social mission. Secondly, SEs largely deliver health care services both independently and in close partnership with public authorities, either through public procurement or by means of direct co-operation agreements. In this perspective, modern welfare systems rely heavily on a significant proportion of health care services and benefits provided by SEs. In addition, in some MSs, such as Italy, SEs are supported by enabling legal frameworks, which also include some important tax benefits. Against this background, the article aims to shed light on the legal aspects and the role of SEs in the delivery of health care services as well as their contribution to ensuring citizens/patients their fundamental right to health.